PRODUCTIVITY AND ACCUMULATION OF HEAVY METALSIN THE GRAIN OF VARIOUS GENOTYPES OF SPRING BARLEY UNDER CONDITIONS OF SOIL CONTAMINATION WITH COPPER AND LEAD - Alybayeva R. A.,; Kalmakhan M. N.,; Inelova Z. A.,; Atabayeva S. D.,; Akhambayeva N. S.,; Autkhanova N. M., (Academic Journal of Physical and Chemical Sciences, 2021)
Environmental pollution, especially by chemical substances, is one of the most powerful factors in disrupting components of the biosphere. Currently, the biosphere receives a lot of pollutants. Among them are significant heavy metals. Among the chemical elements, heavy metals are the most toxic. The danger of increasing the content of heavy metals in the soil and heavy metals in the atmosphere is associated with active absorption and accumulation of plants, which not only negatively affect their active actions, but also threaten human and animal health. The danger of metals is that they have a cumulative effect and retain these toxic properties for a long time. In connection with the task of studying the gene pool of cultivated plants in the conditions of technogenic pollution, the study of metal resistance of barley varieties was carried out in order to identify promising forms for growing in the East Kazakhstan region, as well as breeding donors that collect the minimum amount of pollutants. The results obtained allow us to suggest donors resistant to heavy metals that can be used in breeding and genetic research. Barley is a concentrated product for animals, as the composition is rich in starch and protein. Barley seeds, along with amino acids, protein, lysine and tryptophan, which cannot be replaced by another substance, are preserved better than in other crops. Barley in Kazakhstan ranks second after wheat. The East Kazakhstan region is favorable and in demand for growing barley. However, the damage to the vessels by heavy metal affected the commissioning of the product. The most effective way out of this is to prevent the genetic and physiological effects of the genes of these tolerant (hardy) species. Genotype identification is a new and unexplored area of invention for products that grow against heavy metals in plants.